KUASA HAK IJBAR TERHADAP ANAK PEREMPUAN PERSPEKTIF FIQH DAN HAM - Robbi Izzati, Arini (Islamic University of Indonesia, 2010)
This article discusses the rights of carers based on the opinions ijbar priest sect. Authorization rights ijbar guardian provide more authority for a guardian to marry off their daughters without first asking approval from the child. This is because a guardian is considered the most knowledgeable people about what is best for his daughter, so this happiness perspective formulated by the guardian. Women are considered not proficient in formulating the best things for him. Therefore, her consent is not a priority. In this case a gap between girls and parents, where full power is finally monopolize the interests of women. Right ijbar guardian has the potential to cause various kinds of violence against women which was distanced from the goals of marriage itself. Luckily the Marriage Law in Indonesia does not recognize the concept of rights ijbar. Just as education in the pesantren, one of the institutions of informal education, education curriculum was introduced that the materials are biased patriarchy. Book uqud dul lujain for example, used as the principal study on marriage presented with even marginalize women disproportionately. Keywords: wali, ijbar, pernikahan, keluarga, dan HAM